KONSEP KHIYAR IMAM MALIK BIN ANAS DALAM KITAB AL-MUDAWWANAH AL-KUBRA DAN IMPLEMENTASINYA DALAM TRANSAKSI KEUANGAN KONTEMPORER - Rafiqah, Rafiqah (Moderation | Journal of Islamic Studies Review, 2025)
This research presents a discussion of the existence of the position of Khiyar in buying and selling transactions according to the Maliki Mazhab written in the book Al-Mudawwanah Al-Kubra Volume III, as well as its relevance to the implementation of Khiyar in contemporary buying and selling transactions. The method used in this research is the descriptive method, which is literature. The results of this research are that according to Imam Maliki, the concept of khiyar is inseparable from the position of the existence of buying and selling transactions that have developed as the main contract. The position of khiyar is relative, which means that some economic actors can apply and negate it because it creates uncertainty. Thus, the concept of khiyar exists as a complementary requirement and its absence in a transaction does not affect its validity. However, its existence is the best way to make the contract more valid and ideal and achieve the benefit level for the parties who carry it out.